Evaluation of the American version of the 30-item Endometriosis Health Profile (EHP-30). - Jenkinson, C; Kennedy, S; Jones, G (2008)
OBJECTIVES: Health status instruments, which measure the subjective functioning and well-being of respondents, are increasingly being used in international, multi-centre trials of new treatments. If the results of such trials in different countries are to be pooled, it is vitally important for researchers to know how comparable the instruments are across cultures. In this study, we evaluated the response rate, data quality, score reliability and scaling assumptions of the 30-item Endometriosis Health Profile (EHP-30) in the USA. METHODS: Data were obtained from a multi-centre study which recruited 225 patients from 43 clinic sites in the United States of America. It was a randomised, evaluator-blinded, Phase III study. In the evaluation of the EHP-30 reported here, the two groups (Depot Medroxyprogesterone Acetate [DMPA] and Leuprolide Acetate [LA]) are combined, and analyses are based on the data gained at baseline. Questionnaires were self-completed by patients when they visited the clinics. RESULTS: Data completeness was very high, with 97.33% of respondents completing all of the items on the EHP-30. Furthermore, there were no more than a maximum of two missing responses for any given item. No floor and ceiling effects were found for any of the dimensions of the questionnaire. Internal consistency reliability was high for all dimensions (alpha ranged from 0.84 to 0.91). The psychometric properties of the instrument, outlined in the development of the UK version, are supported in the American context. CONCLUSIONS: The data presented here suggest that the EHP-30 is a valid and reliable measure that can be appropriately and meaningfully used in studies that include respondents from the USA.